2020
DOI: 10.1002/jbmr.4311
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bolus Vitamin D3 Supplementation on Distal Radius Fracture Healing: A Randomized Controlled Trial Using HR-pQCT

Abstract: Vitamin D is an important factor in bone metabolism. Animal studies have shown a positive effect of vitamin D3 supplementation on fracture healing, but evidence from clinical trials is inconclusive. A randomized controlled trial was performed to assess the effects of vitamin D3 supplementation on fracture healing using HR‐pQCT–based outcome parameters. Thirty‐two postmenopausal women with a conservatively treated distal radius fracture were included within 2 weeks postfracture and randomized to a low‐dose (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…A controlled study however could not demonstrate a radiological advantage of vitamin D supplementation for elderly subjects with vertebral fractures [27]. In line with these data, a new small-scale study showed no effect on bone characteristics after a low bolus dose of vitamin D, whereas a higher dose suggested even a negative effect on bone mineral density or strength [28]. Therefore, it is plausible that severe vitamin D deficiency could impair optimal bone mineralization of a healing fracture, but there is no consensus about the benefits of vitamin D for fracture healing in patients with modest vitamin D status.…”
Section: Consequences Of Vitamin D or Calcifediol Deficiency Musculos...mentioning
confidence: 84%
“…A controlled study however could not demonstrate a radiological advantage of vitamin D supplementation for elderly subjects with vertebral fractures [27]. In line with these data, a new small-scale study showed no effect on bone characteristics after a low bolus dose of vitamin D, whereas a higher dose suggested even a negative effect on bone mineral density or strength [28]. Therefore, it is plausible that severe vitamin D deficiency could impair optimal bone mineralization of a healing fracture, but there is no consensus about the benefits of vitamin D for fracture healing in patients with modest vitamin D status.…”
Section: Consequences Of Vitamin D or Calcifediol Deficiency Musculos...mentioning
confidence: 84%
“…A fnal total of 14 studies, assessing a total of 2734 patients, were included to assess fracture outcomes following vitamin D supplementation [10,14,[23][24][25][26][27][28][29][30][31][32][33][34]. Nine of these were controlled trials of which seven were randomised and two were nonrandomised.…”
Section: Resultsmentioning
confidence: 99%
“…Te remaining four studies found no signifcant diferences between the majority of functional outcome scores [10,26,27,29]. Te study by Ko et al was graded as "fair," while the control trials ranged from "low risk of bias" to "serious concerns" [27].…”
Section: Functionalmentioning
confidence: 96%
See 1 more Smart Citation
“…Vitamin D is an important factor in bone metabolism. Animal studies have shown that vitamin D3 supplementation has a positive effect on fracture healing ( 38 ). A clinical study found that serum FGF19 levels were negatively correlated with body weight and hip BMD in older adults older than 60 years ( 39 ).…”
Section: Fgf19 Subfamily In Metabolic Syndrome (Mets)mentioning
confidence: 99%